Saphenofemoral recurrence from an an anatomist’s point of view - Brenner, Erich (Phlebologie, 2020)
From an anatomical point of view, recurrences at the saphenofemoral junction (SFJ) could result from various sources. For one, it could be caused by a recanalisation of an originally occluded great saphenous vein (GSV). Secondly, another vein in the junction region could take over the function of the GSV and dilate. A third variation is a – more or less successful – generation of a new vein. In the last case, a sufficient vein could be generated, an insufficient vein could arise, or an inadequate venous regeneration, so that a cluster of frail but incomplete vasculature remains (neovasculature).Rezidive im Bereich der Krosse, dem Einmündungsbereich der V. saphena magna, können aus anatomischer Sicht aus verschiedenen Quellen stammen. Einerseits kann es sich um eine Rekanalisation einer ursprünglich verschlossenen V. saphena magna handeln. Zweitens kann eine andere Vene der Krossenregion die Funktion übernehmen und dilatieren. Als dritte Variante kommt eine – mehr oder minder gelungene – Neubildung infrage. Im letzteren Fall kann es zur Neubildung einer suffizienten Vene kommen, es kann eine insuffiziente Vene entstehen oder aber es gelingt keine hinreichende Venenbildung und es bleibt bei büschelartigen, zarten, aber völlig inkompletten Gefäßchen (Neovaskularisate).
Keywords: great saphenous vein; varices; recurrence; accessory saphenous veins; neovascularization